Wellbeing in Brass Bands: The Benefits and Challenges of Group Music Making - Williamson, Victoria J.; Bonshor, Michael (Frontiers in Psychology, 2019)
The wellbeing impacts of group music making have been established by evidence-based research. However, studies have largely focused on one group music activity; singing in choirs. To what extent can these wellbeing impacts be considered representative of group music making? This paper presents a survey of wellbeing impacts in brass band players. A wellbeing survey was designed to obtain qualitative information as well as quantitative data for computing descriptive statistics regarding both positive and negative impacts of group music making on wellbeing. The survey was distributed via Brass Bands England and 346 adult brass band players reported self-perceived wellbeing impacts across 5 categories; physical, psychological, social, emotional and spiritual. Responses were analyzed through a descriptive statistical approach combined with an applied thematic analysis that identified the wellbeing impacts expressed by the performers, as well as their valence (positive vs. negative). Areas of overlap between choral practice and brass band work were identified, most notably in the categories of physical, psychological and social wellbeing; enhanced respiratory function and posture, reduced stress, improved general mental health, and regular social interaction. We also identified wellbeing themes that are less common in choral research, impacts relating to the brass bands’ physical demands, competitive tradition, community roles and cross-generational social structures. Based on findings, we created a visual model of group music making impacts across five wellbeing categories as a basis for future research. A wider appreciation of the relationships between group music making and wellbeing can be achieved by expanding the present research base to varied music ensembles and adapting the present model to emerging findings. Testing in this systematic way would enhance understanding of the general wellbeing impacts of group music making that might be accounted for by universal brain and body processes versus wellbeing impacts that may be unique to different ensemble types due to their particular performance styles, practice demands and traditions.